Lt Col Debashish Saha, FCPS, Classified Specialist in Pathology, CMH Bogra (Journal of Armed Forces Medical College, Bangladesh, 2009)
doi: 10.3329/jafmc.v5i1.2839 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.3